Women’s Politics in La Galigo: A Bugis Manuscript - Nurhamdah Zain; Rahmi Djafar; Nur Nahdiyah; Norhan Farouk; Nabilahumaida (IAFOR Journal of Cultural Studies)
This study investigates the political roles of women and gender constructions in La Galigo, an epic central to Bugis culture. Contrary to contemporary gender norms, which often marginalize women’s political participation, La Galigo portrays women as influential decision-makers in governance and state affairs. Employing a qualitative, textual analysis, the study focuses on key female figures in the manuscript, such as Datu’ Palingeq, We Nyili’ Timo, and We Adi Luwu, examining their roles in political leadership, diplomacy, and governance. The analysis highlights how these women challenged the male-dominated power structures typically seen in historical Bugis society. The findings suggest that women’s contributions were valued in political spheres, reflecting a cultural framework of gender balance that prefigures modern ideals of gender equality. By examining these representations, the study underscores the importance of literary narratives in shaping gender roles and proposes that revisiting historical portrayals of women in leadership can inform contemporary efforts toward more inclusive political systems.